Ethics Programs and Ethical Culture: A Next Step in Unraveling Their Multi-Faceted Relationship - Kaptein, Muel (Journal of business ethics, 2009)
One of the main objectives of an ethics program is to improve the ethical culture of an organization. To date, empirical research treats at least one of these concepts as a one-dimensional construct. This paper demonstrates that by conceptualizing both constructs as multi-dimensional, a more in-depth understanding of the relationship between the two concepts can be achieved. Through the employment of the Corporate Ethical Virtues Model, eight dimensions of ethical culture are distinguished. Nine components of an ethics program are identified. To assess the relationship between ethics programs and ethical culture, a survey was conducted of 4,056 members of the U.S. working population. The results show that the relationships between the components of an ethics program and the dimensions of ethical culture differ in strength, nature, and significance. Implications for research and practice are discussed.